Determinants of eating behaviour among university students: a case study of UiTM Dungun, Terengganu - Ainol Murtaza, Ain Nurina Syafiah; Wan Ismail, Wan Nur Fatini; Usman, Samsul Bahri; Mohd Fuza, Zatul Iffah; Mahamed Ali, Faliza (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2025)
Poor eating behaviours among Malaysian university students are a pressing public health concern; yet much pre-pandemic evidence under-represents today’s campus realities, including digital cues that shape food choices. This study aimed to identify the key determinants of eating behaviour among students at Universiti Teknologi MARA (UiTM) Dungun, focusing on socioeconomic, environmental, cultural, psychological, and digital influences. Guided by the Health Promotion Model and the Theory of Planned Behavior, a quantitative cross-sectional survey was conducted involving 360 students selected using probability sampling. Analyses showed that psychological factors (particularly stress) were the strongest correlates of irregular eating, followed by environmental conditions such as affordability, availability, and peer norms, while cultural preferences and socioeconomic constraints also contributed. Exposure to persuasive food content on social media and delivery platforms further shaped choices. The findings highlight the need for practical, context-sensitive strategies: improving affordability and availability of healthier foods on campus, providing culturally familiar options, embedding stress-management supports, and leveraging digital platforms to promote healthier norms.